The direct and indirect effect of brand trust and social media marketing on repurchase intention - Fikriah, Nur Laili; Mahendra, Achmad Muzakki (Nur Science Institute, 2024)
Social media marketing is a platform that makes it easier for companies to achieve their goals, namely, build brand trust at a limited cost. Social media marketing makes it easier for consumers to remember the company’s products and increases brand trust, thereby contributing to the indirect effect of repurchase intention. This research examines the role of brand trust as a mediating variable between social media marketing and repurchase intention. The method used in this research is descriptive quantitative and data collection techniques using surveys. The population in this research is Blitar City Jeensneakers consumers, with a sample of 150. Power analysis in this research uses SEM-PLS. The study results show that social media marketing influences brand trust and repurchase intention, brand trust influences repurchase intention, and brand trust can mediate the relationship between social media marketing and repurchase intention.